Geomechanical Characterisation Analysis of Reservoirs Based on Well Logging Data for CO₂ Injection Applications - Rusmaladewi, Fitri; Louhenapessy, Stevy; Hendrawan, Rezki Naufan; Kurnia, Dwi Miftha; Kurniawan, Randy Yusuf (Penerbitan Universitas Trisakti, 2025)
This study investigates reservoir geomechanical characterization for CO₂ injection applications in the Akimeugah Basin using well-logging and 2D seismic data as the basis for constructing a one-dimensional Mechanical Earth Model (MEM) for well FRD2. The main log data used include sonic logs (Vp, Vs), density, and other logs to calculate dynamic elastic parameters, rock strength (UCS, tensile strength), pore pressure, and in-situ stress profiles (Sv, SHmax, Shmin), which are then validated by horizon and fault interpretation from seismic sections. Analysis of stress polygons, stress profiles, and stereonet plots at depths of 3100–4000 ft indicates that the stress regime is dominated by Normal Faulting with a maximum horizontal stress direction (SHmax) of approximately 150°, with no indication of overpressure but with depth-dependent geomechanical sensitivity to changes in injection pressure. The evaluation results show that the deeper interval (around 4000 ft) exhibits higher rock strength, a wider safe pressure window, fracture gradients well above pore pressure, and narrower zones of potential failure, making it the most suitable and safest target for CO₂ injection, while the 3100–3500 ft interval remains prospective but requires stricter pressure control.